ДОСВІД ВИКОРИСТАННЯ ПРОГРАМНОГО КОМПЛЕКСУ LABVIEW У НАВЧАЛЬНОМУ ПРОЦЕСІ ТА У НАУКОВИХ ДОСЛІДЖЕННЯХ - Парфенюк, Василь Григорович (Збірник матеріалів Міжнародної науково-технічної конференції «ПЕРСПЕКТИВИ ТЕЛЕКОМУНІКАЦІЙ», 2016)
Experience of using of LabVIEW software complex in educational process and in research The report provides experience of using of LabVIEW software system in the educational process in the study of digital radio transmission of information and in research. The advantages of this software system in the development of virtual laboratory devices and setting virtual physics experiment are presented.